Some Trace Remains - Fullard, Madeleine (Kronos: Southern African Histories, 2020)
Winterveld is my first cemetery, and it teaches me everything. Day after day, it takes my assumptions, theories and plans and grinds them into the fine dust that eddies in small puffs around the graves in the late afternoon, when the heat cools and a small breeze picks up. Vast, swollen, Winterveld defies all principles of linear and numerical order. Over the years, the cemetery strains and bursts its seams. Graves creep towards the rough fences and the dirt road.Standing at one end, it is not possible to see where the cemetery ends. It is as if some curvature of the earth conceals its limits. It will take you twenty minutes to weave through the graves, shrubs, low trees and thorny grass to get to a point where you can see the opposite side. You may think you are in a rural area, judging from the sounds of livestock, the vegetation, the small plots and scattered homesteads, but Winterveld is just north of Pretoria, right on the periphery of the townships of Soshanguve and Mabopane.It is an unassuming cemetery. Some of the intermittent tombstones are formal granite structures, but most are rough homemade markers, cobbled together with bricks, cement and wood. Many graves are marked only by low mounds of soil, edged with stones picked up in the nearby fields, often adorned with a few old porcelain cups and enamel plates. These chipped pieces of crockery are the most frequent markers of mourning here: this was his cup, this was her plate.